Secure and energy aware routing protocol (SEARP) based on trust-factor in Mobile Ad-Hoc networks. Issue 4 (4th July 2017) - Ali, Syed Salman; Prasad, B. V. V. S.
Abstract: A Mobile ad-Hoc Network is an anthology of nodes which is an infrastructure less network and hence can be easily established and deployed instantly. In addition to their normal operation, the entire nodes in this breed of network act as routers as well. Because of the mobility and dynamic nature of the network, the entire nodes are liberated to travel indiscriminately and hence topology of a MANET changes very frequently. This invites the complexity of routing the packets from source to destination. Also, as a MANET is a multihop network, the packets should pass through intermediate nodes which always need not be genuine all the time which poses many security issues in MANET's. And all nodes are self-configurable runs on limited capacity battery sources these may possess security and routing issues. Our paper discusses a secure and energy aware routing protocol by considering the nodes mobility and trust-level of a node and implemented our method SEARP using NS2.